A NEW EDUCATIONAL PARADIGM AS AN IMPORTANT FACTOR OF SOCIAL DIRECTION OF ECONOMIC DEVELOPMENT - Kutsenko, Vira; Kinash, Iryna Petrivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
Abstract.The formation of a high-quality socio-economic environment, the main feature of which is a social orientation, is a central element of the quality of life and development of a modern highly developed economy. In achieving this, an important role is given to the educational sphere, which is one of the branches, which ensures the reproduction of the main productive force of society - a person, a worker, and also contributes to the socialization of the economy. In modern conditions, activities in the field of education must necessarily be associated with scientific activities, and above all, this applies to higher education. In the proposed article, based on a review of literary sources, a generalization of scientific approaches to disclosing the role of the educational sphere in ensuring the social orientation of economic development is carried out, the author's position on understanding this process is formulated. Based on the analysis of official statistics, a retrospective review of the development processes of the human resources potential of Ukrainian science and the education costs in general, including higher education, was carried out. As a result of this, it was concluded that negative phenomena prevail in Ukrainian education at the present stage of its development. Based on this, a provision was formulated on the need to form a new paradigm for the development of education and a conceptual vision of this provision was substantiated. In the future, the idea of developing a new education paradigm for our country, will identify the factors that affect the development of education and the educational level of the population, which, in turn, contribute to the formation of a knowledge economy and socialization of the economy. The main problems of the development of education in Ukraine are highlighted, due to the low quality of educational services provided to the population and employers. In this regard, social risks and social security levels are identified. The author's approaches to improving the quality of education and training, accelerating the socialization of the economy, the formation of a knowledge economy on an innovative basis, which will be of great social importance, are formulated.